2009
DOI: 10.3922/j.psns.2009.2.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and education level on the Trail Making Test in a healthy Brazilian sample.

Abstract: The Trail Making Test (TMT) has been a useful tool for neuropsychological assessment. The present study analyzed the influence of age and education level on TMT performance in healthy adult Portuguese speakers. The criteria for exclusion were a history of neurological disease, psychiatric illness, substance abuse, learning disabilities, or any other difficulty that may interfere with testing. The sample (n = 318) was divided into four age groups: (i) very young (n = 92; 18-34 years old), (ii) young (n = 66; 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 17 publications
8
49
3
4
Order By: Relevance
“…It is not surprising to find different Arabic TMT scores in the present study compared with those reported by other countries (Bhatia et al, 2007;Giovagnoli et al, 1996;Hamdan & Hamdan, 2009;Zalonis et al, 2008). Even when constructing TMT-B using characters of the native language instead of the English alphabet, normative data from different countries or cultures are not equivalent for comparable age and education level (Fernandez & Marcopulus, 2008).…”
Section: Discussioncontrasting
confidence: 56%
“…It is not surprising to find different Arabic TMT scores in the present study compared with those reported by other countries (Bhatia et al, 2007;Giovagnoli et al, 1996;Hamdan & Hamdan, 2009;Zalonis et al, 2008). Even when constructing TMT-B using characters of the native language instead of the English alphabet, normative data from different countries or cultures are not equivalent for comparable age and education level (Fernandez & Marcopulus, 2008).…”
Section: Discussioncontrasting
confidence: 56%
“…When the results in this area were compared, there was a statistically significant difference in all results, except in Digit Span (forward) and Stroop test III. Hamdan and Hamdan 24 examining the influence of age and EL on Trail (A and B) test performance in 318 healthy adults aged between 18 and 81 years, divided according to education, reported that the less educated group needed more time to complete the task suggesting that at least more than two years of formal education would be necessary for the test completion. Hashimoto et al 25 study with older people concluded that there is a need for at least six years of schooling to the test set.…”
Section: Discussionmentioning
confidence: 99%
“…Among the MCI patients, 13 had single-domain amnestic MCI and 15 had multipledomain amnestic MCI. Patients in this unit undergo a vast battery of psychometric instruments biannually that assess cognitive and functional skills. (Nelson, 1976), Trail Making tests A and B (Hamdan & Hamdan, 2009), and Vocabulary and Block Design subtests of the Wechsler Adult Intelligence Scale, revised (WAIS-R; Nascimento & Figueiredo, 2002).…”
Section: Participantsmentioning
confidence: 99%